Liquefied petroleum gas monitoring and leakage detection system using nodemcu ESP8266 and wi-fi technology - Suzi Seroja Binti Sarnin; Divine Senanu Ametefe; Nani Fadzlina Naim; Wan Norsyafizan Wan Mohamad; Norlela Ishak; Norfishah Ab Wahab; Norsuzila Ya’acob (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Liquefied Petroleum Gas which is popularly known as LPG is a clean source of energy which is highly flammable and usually compressed into storage tanks. Due to the flammable nature of LPG it can easily lead to uncontrollable explosions in the presence of any ignition action or may lead to complete depletion of oxygen in a particular area. This study is focused on the fabrication of a system that would detect, monitor and control LPG gas leakages for domestic gas cylinders. A MQ-2 gas sensor was used for the detection of LPG gas leakages, the monitoring aspect was satisfied locally through notifications triggered by LEDs, piezo buzzer and remotely through the use of an application known as Blynk. The control aspect was implemented with the use of a stepper motor which turns off gas cylinder regulators whenever gas concentrations are high. All operations are primary hinged on the NodeMCU ESP8266 controller and Wi-Fi communication technology.